Good governance and cooperative societies: provisions and recommendations for the good governance of cooperative societie - Sánchez Pachón, Luis Ángel (Cooperativismo & Desarrollo, 2019)
The concern for good corporate governance has not been absent in the cooperative sector. Many of the problems pointed out in the structure and functioning of cooperatives are common within private equity firms, although they are evidently under different parameters. It is therefore appropriate to examine the proposals on corporate governance, which, although centralized in the governance of listed companies, have been elaborated in recent years, driven by changes in economic and social reality. In this analysis, it is a priority to know the perspective or approach of good corporate governance that follows (shareholder or monistic vs. pluralist or stakeholders), as well as the proposed legal technique (legislative intervention versus self-regulation through which one knows as Codes of Good Government) . In this paper, after outlining some conceptual aspects, we describe how the ideas of corporate governance have been incorporated into Spanish law; we highlight the main steps in the search for the construction of good corporate governance and analyze some concrete proposals of good governance that, from different scopes, have been directed, in particular, to cooperative societies.
Keywords: corporate governance; shareholders; stakeholders; interest groups; Code of Good Government